Myrmecophilus balcanicus, a new species of ant-loving cricket from the Former Yugoslav Republic of Macedonia, with notes on the synonymy of Myrmecophilus zorae - Stalling, Thomas (ENTOMOLOGIA HELLENICA, 2013)
A new species of ant-loving cricket, Myrmecophilus balcanicus sp. n., is described and illustrated based on individuals collected in the Former Yugoslav Republic of Macedonia (FYROM). It’s habitat is described. The species belongs to the subgenus Myrmecophilus Berthold, 1827. Myrmecophilus zorae Karaman, 1963 is recognized as a junior synonym of Myrmecophilus hirticaudus Fischer von Waldheim, 1846.